2023
DOI: 10.1192/bjp.2023.43
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 susceptibility and COVID-19 illness course and outcome in people with pre-existing neurodegenerative disorders: systematic review with frequentist and Bayesian meta-analyses

Muhannad Smadi,
Melina Kaburis,
Youval Schnapper
et al.

Abstract: Background People with neurodegenerative disease and mild cognitive impairment (MCI) may have an elevated risk of acquiring severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and may be disproportionally affected by coronavirus disease 2019 (COVID-19) once infected. Aims To review all eligible studies and quantify the strength of associations between various pre-existing neurodegenerative disorders and both SARS-CoV-2 susceptibility and COVID-19 illness course and outcome. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 179 publications
0
3
0
Order By: Relevance
“…A recent systematic review and meta-analysis found that PD patients were at a higher risk of contracting SARS-CoV-2 (OR = 1.65 (1.34–2.04), especially if they were cognitively impaired [ 32 ]. An observational, retrospective, multicenter study ( n = 552) showed that the incidence of COVID-19 was significantly higher among PD patients who were younger than 50 and had shorter durations of disease or had less-advanced PD [ 33 ].…”
Section: Is Covid-19 More Common Among Parkinson’s Disease Patients?mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review and meta-analysis found that PD patients were at a higher risk of contracting SARS-CoV-2 (OR = 1.65 (1.34–2.04), especially if they were cognitively impaired [ 32 ]. An observational, retrospective, multicenter study ( n = 552) showed that the incidence of COVID-19 was significantly higher among PD patients who were younger than 50 and had shorter durations of disease or had less-advanced PD [ 33 ].…”
Section: Is Covid-19 More Common Among Parkinson’s Disease Patients?mentioning
confidence: 99%
“…Five systematic reviews and meta-analyses explored mortality rates among PD patients with COVID-19, concluding that PD may be associated with increased mortality and poor outcomes [ 32 , 35 , 36 , 37 , 67 ]. Although initial estimations varied greatly due to the small number of patients, the study design and the excessive heterogeneity of the collected data, the mortality rate of affected PD patients seems to be somewhere between 18 and 25% [ 31 ].…”
Section: Does Covid-19 Increase the Hospitalization Rate Or Mortality...mentioning
confidence: 99%
“…The potential impact of SARS-CoV-2 infection on the development and progression of neurodegenerative disorders is a growing area of concern and interest [ 5 ]. Neurodegeneration, a term encompassing a heterogeneous group of disorders characterized by progressive loss of neuronal structure and function, poses a significant global health challenge [ 6 ]. These disorders rank among the leading causes of disability and mortality worldwide, imposing a substantial burden on healthcare systems and society.…”
Section: Introductionmentioning
confidence: 99%